Serum malondialdehyde and serum glutathione peroxidase levels in pregnant women with and without preeclampsia - Yanglem, Ajitkumar S.; Koch, Niren S.; Naorem, Sangeeta; Kshetrimayum, Roshita D.; Kamei, Guiphiuliu; Nongmaithem, Bidya; Okram, Reshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Preeclampsia is a pregnancy-specific disorder that affects 10% of all pregnancies which contributes heavily to maternal mortality and perinatal morbidity. Several studies have shown that oxidative stress plays an important role in the pathogenesis of preeclampsia. However, the association has not been proven indisputably. So, the study was done with the view to determine serum malondialdehyde and glutathione peroxidase levels in pregnant women with and without preeclampsia and to compare the levels between the two groups of participants. Methods: This is a cross-sectional study conducted in the Department of Biochemistry and Department of Obstetrics and Gynaecology, RIMS. 55 preeclamptic patients and 55 pregnant women without preeclampsia were recruited as cases and controls respectively. Results: Serum malondialdehyde was found to be significantly higher in cases (1280.02±619.55ng/ml) than the controls (826.51±599.84ng/ml) and glutathione peroxidase levels were found to be significantly decreased in the preeclamptic women (224.49±201.29pg/ml) when compared to the normal healthy pregnant women (448±350.54 pg/ml. Serum malondialdehyde levels were found to be positively correlated with blood pressure. Conclusions: Serum malondialdehyde was increased in preeclampsia and serum glutathione levels was decreased in preeclamptic pregnant women when compared to the pregnant women without preeclampsia. Serum malondialdehyde levels were significantly correlated with high blood pressure. The oxidant-antioxidant system may be involved in the etiology of preeclampsia, however the cause and effect relation needs further evaluation.